Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/00365520902803499
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoids promote release of the satiety hormone cholecystokinin while reducing insulin in healthy humans

Abstract: The addition of thylakoids to energy-dense food promotes satiety signals and reduces insulin response during a single meal in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
71
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 24 publications
14
71
2
Order By: Relevance
“…One advantage is the ability of thylakoids to activate gastrointestinal satiety hormones, which may limit overeating. The present experiments have confirmed the ability of thylakoids to promote satiety signalling in healthy humans (Köhnke et al, 2009). Future studies will be performed where thylakoids are given as a food supplement to obese individuals.…”
Section: Discussionsupporting
confidence: 85%
“…One advantage is the ability of thylakoids to activate gastrointestinal satiety hormones, which may limit overeating. The present experiments have confirmed the ability of thylakoids to promote satiety signalling in healthy humans (Köhnke et al, 2009). Future studies will be performed where thylakoids are given as a food supplement to obese individuals.…”
Section: Discussionsupporting
confidence: 85%
“…In a series of previous studies we have found that thylakoid membranes, the photosynthetic membrane in plant cells, inhibit pancreatic lipase/co-lipase in a dose-dependent way in vitro, an effect confirmed both in animal studies on rat 12 and mice 13 as well as in human studies 14,15 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included mentioning
confidence: 59%
“…Previous studies both in animal and human models have shown that when thylakoids were included in foods, satiety hormones such as cholecystokinin (CCK), leptin and enterostatin increased while the hunger peptide ghrelin decreased [12][13][14] . This phenomenon has been attributed to a prolonged lipid digestion, and as long as food is present in the intestine, satiety is promoted 4 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included mentioning
confidence: 99%
“…The hunger hormone ghrelin has been shown to stimulate the uptake of glucose, while cholecystokinin (8) , leptin (9) and resistin (10) inhibit the uptake of glucose. Since thylakoids stimulate the release of cholecystokinin and leptin (6) , it may well be that the observed reduction in blood glucose levels were an effect of these hormones. Another explanation could be that thylakoid membranes have a direct effect on glucose uptake, by interacting with the intestinal absorptive surface.…”
mentioning
confidence: 99%
“…chloroplast membranes from green leaves, retard fat digestion both in vitro and in vivo (4) . This retardation in turn stimulates the release of satiety hormones, such as cholecystokinin (4,5) and leptin (6) , while reducing the hunger hormones ghrelin and insulin (6) . The long-term effect of thylakoid administration was thus a reduced food intake and body weight, as demonstrated both in mice (5) and in rat models (4) .…”
mentioning
confidence: 99%